Stability assessment for hard anti-inclined bedded rock slopes using a limit equilibrium method - Qu, Xin; Diao, Fangfang (Frontiers in Earth Science, 2022)
The failure mechanism of hard anti-inclined bedded rock slopes with the possibility of undergoing flexural toppling is very complex so that it is difficult to effectively perform their stability assessment. In this study, an attempt was made to accurately predict the stability factor and the failure surface of such slopes: establishing a new failure zone model and developing a limit equilibrium method based on this model. In this model, the failure zones of such a slope were divided strictly according to the failure mechanisms of the rock layers. In the presented method, the failure surface was considered to be a bilinear-type surface as observed in field investigations and laboratory tests, and the non-dimensional parameter indicating the position of application of the interlayer force was revised by deriving the distribution and the equivalent substitution of interlayer force. Then, a comparative study on Yangtai slope was performed to prove the presented method, and the effect of the non-dimensional parameter on the stability was also investigated. The results reveal that the presented method can accurately determine the failure surface and precisely evaluate the slope stability factor. In addition, the presented method has higher predictive accuracy compared with other analytical methods. With the decrease of the non-dimensional parameter, the stability of the slope is reinforced, but the larger landslide with more serious damage effect will occur if the slope undergoes the overall failure.